Comparative in vitro activity of meropenem versus other routinely used antimicrobials against 18 632 aerobic bacteria tested in 92 German centers - Geiss, Heinrich K.; Beck, G. (International journal of antimicrobial agents, 1998)
The in vitro antibacterial activity of meropenem and up to 26 other antibiotics was compared under routine conditions at 92 German centers from March to June 1995 with use of the agar diffusion method against 18 632 recent isolates from ICU—hemato-oncology—and pediatric patients. Overall, meropenem was the most active drug exhibiting a higher activity against gram-negative aerobes than imipenem, but somewhat less active against staphylococci and enterocooci. The overall resistance rates of most antibiotics tested was higher compared to the recently published surveillance data of the Paul-Ehrlich-Society in Germany. The main reason for this discrepancy is the higher percentage of test strains which were recovered from intensive care unit patients in the present study. These data confirm similar results from the USA and underscore the pressing need for the implementation of a nationwide antimicrobial surveillance system which is risk-stratified by hospital size, ICU- versus non-ICU-patients, and body site from which the isolates are recovered.
Gesehen am 13.03.2025